Genetic lineage tracing in clonal haematopoiesis and myeloproliferative neoplasms - Sousos, N (2023)
Clonal haematopoiesis (CH) is a common age-related condition in which somatic mutations accumulate in haematopoietic stem and progenitor cells (HSPCs), leading to the clonal expansion of mutated cells. This process has been causatively linked with atherosclerotic cardiovascular disease and related complications, while it has also been associated with an increased risk of development of myeloid neoplasms, including myeloproliferative neoplasms (MPNs). This DPhil thesis aimed to investigate the pathogenesis of CH and MPNs utilising genetic lineage tracing.